Submillisievert CT angiography for carotid arteries using wide array CT scanner and latest iterative reconstruction algorithm in comparison with previous generations technologies: Feasibility and diagnostic accuracy - Annoni, Andrea Daniele; Montorsi, Piero; Andreini, Daniele; Pontone, Gianluca; Mancini, Maria Elisabetta; Muscogiuri, Giuseppe; Formenti, Alberto; Mushtaq, Saima; Trabattoni, Piero; Dainese, Luca; Pepi, Mauro (Journal of cardiovascular computed tomography, 2019)
To assess evaluability and diagnostic accuracy of a low dose CT angiography (CTA) protocol for carotid arteries using latest Iterative Reconstruction (IR) algorithm in comparison with standard 100 kVp protocol using previous generation CT and IR. 105 patients, referred for CTA of the carotid arteries were prospectively enrolled in our study and underwent CTA with 80 kVp and latest IR algorithm (group 1). Data were retrospectively compared with 100 consecutive patients with similar examination indications that had previously undergone CTA of carotid arteries with a standard 100 kVp protocol and a first generation IR algorithm (group 2). Image quality was evaluated with a 4-point Likert-scale. For each exam CT number, image noise, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR) at level of common carotid artery (CCA), internal carotid artery (ICA) and at level of Circle of Willis and Effective Dose (ED) were evaluated. 62 Group 1 patients underwent a clinically indicated DSA and results were compared with CTA. No exams reported as not diagnostic. The overall mean CT number value of all arterial segments was above 450 HU in both groups. Significant lower noise, and higher SNR and CNR values were found in group 1 in comparison with group 2 despite the use of 80 kVp. In 62-group 1 patients studied by DSA, CTA showed in a segment-based analysis a sensitivity, negative predictive value and accuracy of 100%, 100% and 99% respectively. Mean ED in group 1 was 0.54 ± 0.1 mSv with a dose reduction up to 86%. CTA for carotid arteries using latest IR algorithm allows to perform exams with submillisievert radiation exposure maintaining good image quality, overall evaluability and diagnostic accuracy. •Adaptive statistical iterative reconstruction (ASIR)-V allows high-quality low-dose CT.•Use of last generation CT scanner and ASIR-V allows high accuracy examinations.•In comparison with ASIR, ASIR-V allows ED reduction up to 86%.